(3ebGQHI ZRh GdCShGb GdOhdjIs - (3OQhGRj(B, (3jSejfs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jJWQb gPG GdcJGH SJI aUhd ceG jdj(B: (3eONd YGe ddJShjb, eONd ddJShjb GdOhdj, HjFI GdJShjb GdOhdj, HMhK GdJShjb GdOhdj, GdeRjL GdJShjbj GdOhdj, ZRh GdCShGb GdOhdjI(B.s
(3HHdjhZQGajG(B: (3U U(B.147-148s
Keywords: (3GdCShGb GdOhdjIs; (3GdJShjbs; (3GdJShjb GdOhdjs